Review Paper on Face Clustering - Rakhi, Rakhi; Suman, Suman (International Journal of Computer Sciences and Engineering, 2020)
In recent years video surveillance system has been broadly established and nowadays we can see the billions of cameras are embedded in smart phones and other devices. Face investigation from videos and images is most predominant task for various government agencies and industry alike. The process in which unlabeled facial images are assembled according to individual characteristics is called face clustering. Clustering is required in numerous applications for example, law enforcement, disruptive design, construction, social media, health care and surveillance applications etc. Here, in this paper we reviewed some of the face clustering works done by different researchers using different methods for different applications and also gives the brief knowledge about the work done by the previous researcher.